2007
DOI: 10.1016/j.serrev.2006.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Self-Archiving in Institutional Repositories: Depositorship and Full-Text Availability

Abstract: This research evaluates the success of open access self-archiving in several wellknown institutional repositories. Two assessment factors have been applied to examine the current practice of self-archiving: depositorship and the availability of full text. This research discovers that the rate of author self-archiving is low and that the majority of documents have been deposited by a librarian or administrative staff. Similarly, the rate of full-text availability is relatively low, except for Australian reposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 14 publications
0
27
0
1
Order By: Relevance
“…While the idea of the IR is usually well received, asking faculty to self-archive "did not translate into real content being deposited," resulting in stagnating growth (Mackie, 2004, n.p.). Several other studies found self-archiving rates to be low, with the majority of scholarship made accessible by someone other than the researchers themselves (Foster & Gibbons, 2005;Xia & Sun, 2007;Covey, 2009;Covey, 2011).…”
Section: Content Population Via Self-archivingmentioning
confidence: 99%
“…While the idea of the IR is usually well received, asking faculty to self-archive "did not translate into real content being deposited," resulting in stagnating growth (Mackie, 2004, n.p.). Several other studies found self-archiving rates to be low, with the majority of scholarship made accessible by someone other than the researchers themselves (Foster & Gibbons, 2005;Xia & Sun, 2007;Covey, 2009;Covey, 2011).…”
Section: Content Population Via Self-archivingmentioning
confidence: 99%
“…Xia and Sun also stress the importance for IR evaluation of factors such as authors' attitude, information on depositor, usage assessment and interoperability. In a subsequent article Xia and Sun (Xia & Sun, 2007a) develop an evaluation method of repositories based mainly on two assessment factors: depositorship, i.e. depositor identity (which conflates author and editorial processes) and availability of full text.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Organizationally, the responsibility for the administration of the database at NRC-IRC falls under the control of Library and Internet Services (LIS). Recent studies suggest that such IRs are more successful when administrative and maintenance tasks are allocated to people other than the researchers themselves [4]. At NRC-IRC, the LIS staff enters all bibliographic information, creates standardized PDFs for the Web, ''alerts'' clients to new material available and verifies that new publications are indexed by Internet search engines.…”
Section: Backgroundonnrc-irc Fireresearchandthenrc-irc Publications Dmentioning
confidence: 99%